Mechanism and Controlling Factors on Methane Yields Catalytically Generated From Low-Mature Source Rocks at Low Temperatures (60–140°C) in Laboratory and Sedimentary Basins - Wei, Lin; Yin, Jia; Li, Jiansheng; Zhang, Kun; Li, Chunzhen; Cheng, Xiong (Frontiers in Earth Science, 2022)
Various studies have shown that geo-catalytically mediated methanogenesis could happen in immature to early-mature source rocks at temperatures ranging from 60 to 140°C based on a series of long-term laboratory heating experimental evidences. The results of those studies show that methane yields at the given temperature are 5–11 orders of magnitude higher than the theoretically predicted yields from early thermogenic methane generation kinetic models. However, different types of source rocks in these laboratory simulation experiments generated varied CH4 and CO2 yields, which suggest that controls on CH4 generation during catalytic methanogenesis are complex. This study summarizes and compares gas yield results from laboratory low-temperature heating simulation experiments. Pre-existing trapped methane in rock chips could mimic newly generated gas during heating. The yields of catalytically generated CH4 from individual source rocks were re-quantified by subtracting the amounts of pre-existing CH4 in the closed pores of the original source rocks from the total methane amounts released from heating experiments and pre-existing CH4 in the closed pores in heated source rocks. The results show that heating temperature and time exert a positive influence on methane catalytic methanogenesis. Mowry and Second White Specks Formation Shale generated approximately ten times more CH4 than New Albany Shale and Mahogany Shale per gram of total organic carbon (TOC). Samples of Springfield Coal #1 and #2 exhibited ten times yield difference from one another at the same heating temperature. Those yield differences are not strongly associated with TOC content, heating time, temperature, metal content, or kerogen type but appear to be more influenced by maceral composition and also maceral–mineral contact area within the source rocks. We conclude that macerals in the liptinite group have a propensity for methanogenesis. Specifically, amorphous organic matter undergoes transformation into hydrocarbons earlier than alginite at low-temperature heating conditions. Sporinite also contributes to higher yields of methane released from the coal source rock. Vitrinite and inertinite show a positive influence on carbon dioxide but no significant effect on increasing methane yields compared to other macerals. The strongest catalytic methanogenesis in the studied sample produced methane yields at 60°C, which amounted to ∼2.5 μmol per gram of organic carbon during one year of heating. We suggest that geocatalytic methanogenesis could generate economically sizeable gas plays from immature to early-mature source rocks over geologic time.